Breakthroughs in technical analysis new thinking from the world's top minds - Keller, David, 1976-; ProQuest (Firm) (New York : Bloomberg Press, 2007)
"Breakthroughs in Technical Analysis explains the new trading methods used by the world's top technicians, encompassing in one volume the investing approaches of ten proven practitioners. More important, some of these techniques have never left their country's borders before and are not known or used in other parts of the world"--Provided by publisher.
Includes index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Investment analysis; Electronic books